An EDG Method for Distributed Optimal Control of Elliptic PDEs (Advances in Applied Mathematics and Mechanics, 2018)
We consider a distributed optimal control problem governed by an ellipticPDE, and propose an embedded discontinuous Galerkin (EDG) method to approximatethe solution. We derive optimal a priori error estimates for the state, dual state,and the optimal control, and suboptimal estimates for the fluxes. We present numericalexperiments to confirm our theoretical results.